Estimating sugar concentration in human blood serum using Surface Plasmon Resonance (SPR) –based optical fiber sensor - Rahim, Namaa Salem (Iraqi Journal of Physics, 2019)
Surface Plasmon Resonance (SPR)-based plastic optical fiber sensor for estimating the concentration and refractive index of sugar in human blood serum. The sensor is fabricated by a small part (10mm) of optical fiber in the middle is embedded in a resin block and then the polishing process is done, after that it is deposited with about (40nm) thickness of gold metal. The blood serum is placed on gold coated core of an Optical grade plastic optical fiber of 980 µm core diameter.